2004
DOI: 10.1002/pssa.200406899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electronegativity on transport properties of (La0.83M0.17)0.67Ca0.33MnO3 (M = Y, Bi)

Abstract: Electrical transport and magnetic properties of (La0.83M0.17)0.67Ca0.33MnO3 (M = Y and Bi) have been investigated. Experimental results show that the doped samples have obviously different electrical transport and magnetic properties; the difference cannot be interpreted only on the basis of the effect of the ionic radius 〈rA〉, where 〈rA〉 is the average ionic radii of A‐site cations. Together with the ionic radius and the electronegativity of the doping ion, the differences of electrical transport and magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The T C decrease can be attributed to the reduction of the Mn-O-Mn band angle with increase in both /r A S and s 2 [21]. It can also be ascribed to the electronegativity difference in the doping ions [22]. The magnetization as a function of the magnetic applied field at 20 K is shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The T C decrease can be attributed to the reduction of the Mn-O-Mn band angle with increase in both /r A S and s 2 [21]. It can also be ascribed to the electronegativity difference in the doping ions [22]. The magnetization as a function of the magnetic applied field at 20 K is shown in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…This suggests that apart from A-site ionic radii some other parameters influence the physical properties. It appears that electronegativity difference between rare earth (RE) and alkaline earth (AE) ion also affect the transport and magnetic properties [8]. An electronegativity difference between RE and AE elements is large which leads to more ionic character with varying AE ion concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 70 years, the concept of EN has been continuously modified, debated, and expanded. The dependence of many physical and chemical properties of atoms and molecules on EN has led to many correlations, and thus various different EN scales have been proposed. , Simultaneously, comprehensive theoretical studies about various EN scales have been carried out to check their reliabilities, explore their applications, or search for their intrinsic correlations. EN is not only very useful in understanding chemical bonds and explaining many chemical phenomena, but is also of great significance for materials science, in which this parameter is applied to rationalize the geometries and properties of quite complex systems. It has been found that the EN difference among constituent elements is an important factor influencing the stability of the supercooled liquid in glassy alloys .…”
Section: Introductionmentioning
confidence: 99%